Pengaruh Varian Produk, Harga Dan Media Sosial Terhadap Keputusan Pembelian Martabak Boss Di Kota Bengkulu - Danang Andrean, Mohammad; ., Syofian; Puspita, Veny (Ekonomi & Bisnis, 2023)
The purpose this study to find out how much influence product variants, prices and social media on buying decisions for martabak boss Bengkulu. variables study product variants, prices and social media. method used research distributing questionnaires. research quantitative approach research. research population all consumers martabak boss Bengkulu City, 150 samples using saturated sample method. analytical tool used study used SPSS. data analysis method used was multiple linear regression. results showed ( 1) product variant has a significant effect on the purchasing decision of martabak boss Bengkulu City, (2) price has a significant negative effect on purchasing decisions of martabak boss Bengkulu City, (3) social media has no significant effect on purchasing decisions of martabak boss in Bengkulu city, (4) variant product, price and social media have a simultaneous effect on purchasing decisions for martabak boss in Bengkulu City. Keywords: product variants, prices and social media and purchasing decisions